THE INITIATION AND TRANSFORMATIONAL PROCESS OF JACK FROST IN PETER RAMSEYâS RISE OF THE GUARDIANS - Adhyanggono, G.M. (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
Jack Frost may not be as popular as Santa Claus, Easter Bunny, Sandman, and Tooth Fairy in the tradition of Western fairy tales. However, having observed Peter Ramseyâs Rise of the Guardians, it is quite âenlighteningâ to perceive Jack Frost positioned not only as a mere Hollywoodâs animated hero, but as complex one. One of the complexities studied in this case resides in the initiation and transformational process he has to undergo. This article overviews the relation between such process and his position as the archetypal hero. Making use archetypal approach, this article intends to explain the issue. The result indicates that his portrayal in the movie as the archetypal hero experiencing archetypal initiation and transformation is influenced by some factors: interaction with other Guardians and children, quest for self-identity, and his relation with nature.